2018
DOI: 10.23983/mv.69952
|View full text |Cite
|
Sign up to set email alerts
|

Suomi24-keskustelut kohtaamisten ja törmäysten tilana

Abstract: Artikkelissa tarkastellaan Suomi24-foorumikeskusteluita käyttäjien välisen kohtaamisen ja vuorovaikutuksen tilana keskustelukulttuurin ja vallankäytön näkökulmista. Tutkimusaineistona on vuonna 2016 Citizen Mindscapes-hankkeessa toteutetun käyttäjäkyselyn avovastausaineisto, jossa käyttäjät kuvaavat foorumikeskustelujen herättämiä positiivisia ja negatiivisia tunteita sekä pohtivat, mitä heidän elämästään puuttuisi, jos Suomi24-foorumiaei olisi. Käyttäjät kokivat keskustelujen asiattomuuden ja häiriköinnin ras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…As to the question of who typically uses the Suomi24 site, an online survey of forum users ( n = 1395, Dec. 2016; see Harju, 2017) revealed that the majority of users are middle‐aged (40–50 years old) or elderly persons. Sixty‐three per cent of the respondents were male, and 55% were either married, in a registered partnership or cohabiting.…”
Section: Methodsmentioning
confidence: 99%
“…As to the question of who typically uses the Suomi24 site, an online survey of forum users ( n = 1395, Dec. 2016; see Harju, 2017) revealed that the majority of users are middle‐aged (40–50 years old) or elderly persons. Sixty‐three per cent of the respondents were male, and 55% were either married, in a registered partnership or cohabiting.…”
Section: Methodsmentioning
confidence: 99%
“…esim. Harju 2018). Helsingin Sanomien keskustelussa omalla nimellään kommentoi joka viides kirjoittaja, Ylen keskustelussa ainoastaan joka kahdeksastoista kirjoittaja.…”
Section: Aineisto Ja Menetelmätunclassified
“…It is one of the largest non-English discussion forums in Europe, offering an open-access corpus on posts discussing a variety of topics. The survey conducted by Harju (2018) revealed that the users of Suomi24 consider it as a platform where ordinary people can express their views that often go unheard in the mainstream media. Suomi24 is divided into 21 main subforums under headings such as “Family,” “Entertainment and Culture” and “Health.” The latter includes many subgroups, for example, “Vaccinations.” The users can submit posts anonymously, but the discussion threads are moderated in order to prevent incivility.…”
Section: Empirical Datamentioning
confidence: 99%